Prevalence of menstrual symptoms change and influencing factors among international female students studying in china during acculturation period - Asem Alkhatib; Qidi Zhou; Ousman Bajinka; Ratee Pakwan Suwal; James Wiley; Xianhong Li (BMC, 2022)
Abstract Background A number of previous studies have explored international students' adaptation process with regards to language, lifestyle, food, and environment. However, there have yet been no studies conducted to address the menstrual symptoms challenges faced by international female students during the acculturation period. Thus, this study aims to describe the prevalence of menstrual symptoms change and to explore the influencing factors among international female students studying in China during the acculturation period. Methods An online cross sectional study was conducted among international female students studying in China during the acculturation period (defined as the first six months of living in the host country) in Hunan Province of China from March 2019 to July 2019. Menstrual symptoms questionnaire, sociocultural adaptation scale, China higher education student satisfaction scale, perceived stress scale, and Pittsburgh sleep quality index were used for data collection. Descriptive analysis, ANOVA, paired t-test, Pearson correlation, and multivariate linear regressions were used to analyze the data using SPSS 21.0 software. Results Three hundred and forty-five (97.18%, 345/355) female students from 45 countries fully completed the questionnaire. The mean age of the participants was (26.59 ± 6.439) years. In total, 18.49% of participants had encountered menstrual symptoms change. There were significant differences in the menstrual symptoms score between before arrival and evaluation during the first six months of living in China (t = − 11.700, p = 0.000). The main menstrual symptoms change included cramps (17.68%), irritation (14.78%), abdominal pain (12.46%), fatigue (12.46%), and headaches (9.85%). Cultural adaptation level (β = 0.198, 95% CI: 0.934, 2.995), sleep quality (β = 0.166, 95% CI: 0.112, 0.496), perceived stress (β = 0.193, 95% CI: 0.123, 0.410), time spent in the host environment, (β = − 0.270, 95% CI: − 3.200, − 1.444) and experience of visiting foreign countries (β = 0.184, 95% CI: 1.134, 4.125) were significantly correlated with menstrual symptoms change. Conclusion The prevalence of menstrual symptoms change among international female students should not be overlooked when considering menstrual health in this population. Poorer cultural adaptation, poorer sleep quality, higher stress, and lack of overseas living experiences significantly influence the menstrual symptoms of international female students studying in China.